Construction and Validation of the Research Misconduct Scale for Social Science University Students - Ghayas, Saba; Hassan, Zaineb; Kayani, Sumaira; Biasutti, Michele (Frontiers in Psychology, 2022)
The current study aims to construct and validate a measure of research misconduct for social science university students. The research is comprised of three studies; Study I presents the scale construction in three phases. In Phase I, the initial pool of items was generated by reviewing the literature and considering the results of semi-structured interviews. Phase II involved a psychometric cleaning of items, after which 38 items were retained. In Phase III, those 38 items were proposed to 652 university students and data were exposed to exploratory factor analysis, which extracted a one-factor structure with 15 items and 55.73% variance. Study II confirmed the factorial structure of the scale using an independent sample (N = 200) of university students. Confirmatory factor analysis of the scale demonstrate a good model fit to the data with the one-factor structure established through the exploratory factor analysis. The scale exhibits good internal consistency, with a Cronbach’s alpha of 0.95. Study III involves validation of the scale, with evidence for convergent validity collected from a sample of university students (N = 200). The results reveal that the research misconduct scale has significant positive correlations with academic stress and procrastination and a significant negative correlation with academic achievement. The obtained convergent validity testifies that the scale can be considered a psychometrically sound instrument to measure research misconduct among social science university students.